Cardio-renal effect of dapagliflozin and dapagliflozin- saxagliptin combination on CD34 + ve hematopoietic stem cells (HSCs) and podocyte specific markers in type 2 diabetes (T2DM) subjects: a randomized trial - Seshagiri Rao Nandula; Arad Jain; Sabyasachi Sen (Stem Cell Research & Therapy)
Abstract Introduction Effects of Dapagliflozin (Dapa) and Dapagliflozin-Saxagliptin combination (Combo) was examined on peripheral blood derived CD34 + Hematopoetic Stem Cells (HSCs) as a cellular CVD biomarker. Both Dapa (a sodium-glucose co-transporter 2 or SGLT2, receptor inhibitor) and Saxagliptin (a Di-peptydl-peptidase-4 or DPP4 enzyme inhibitor) are commonly used type 2 diabetes mellitus or T2DM medications, however the benefit of using the combination has not been evaluated for cardio-renal risk assessment, in a real-life practice setting, compared to a placebo. Hypothesis We hypothesized that Dapa will improve the outcomes when compared to placebo and the Combo maybe even more beneficial. Methods This is a pilot study evaluating low dose Dapagliflozin 10 mg or low dose Dapa + low dose Saxagliptin combination. 15 subjects were enrolled in 16 weeks, double-blind, three-arm, randomized placebo matched trial, with 10mg Dapa + Saxa placebo (n = 4), 10 mg Dapa + 5 mg Saxa (n = 5) Combo, And Dapa placebo + Saxa placebo (n = 6), Placebo groups. T2DM subjects (age 30–70 yrs) with HbA1c of 7–10%, were included. CD34 + HSC number, migration, mRNA expression along with biochemistry and urine exosomes were measured. Data were collected at week 0, 8, and 16. For statistics, a mixed model regression analysis was used. Results Significant HbA1c (p = 0.0357) reduction was noted in Combo group versus Dapa alone and Placebo. hsCRP levels (P = 0.0317) and IL-6, two important inflammatory molecules, were significantly reduced in both Dapa and Combo vs. Placebo. Leptin levels decreased significantly in both Dapa alone (p = 0.035) and Combo group(p = 0.015), vs. Placebo, however the Adiponectin levels were higher in Dapa alone group. Dapagliflozin alone reduced lipid parameters significantly particularly triglyceride (TG) when compared to placebo, with resultant visit 3 values at 99.5 ± 7.2 vs. 129 ± 12.3 and LDL/HDL ratio values were similar at 2.18 ± 0.08 vs. 2.13 ± 0.15. CD34 + cell migration improved significantly in both Dapa alone (p = 0.05) and Combo group (p = 0.05) vs. Placebo. Conclusions Several parameters showed significant improvement with both Dapa alone and Combo compared to placebo. However, when all outcome measures were taken into account, other than glycemic control the Combo didn’t seem to offer any further benefit, over Dapa alone. Therefore, contrary to our initial hypothesis we do not believe the more expensive Dapa + Saxa combination offers any specific cardiovascular benefit compared to Dapagliflozin alone. However it is noteworthy that both Dapa and its combination with Saxagliptin showed significant improvement compared to placebo in T2DM, particularly when progenitor cell based numbers and function were analyzed and taken into account. Trial Registration The trial was registered with Clinical Trials.gov number NCT03660683, last updated 06052023.